2016
DOI: 10.1177/1540415316631504
|View full text |Cite
|
Sign up to set email alerts
|

Access Barriers to Prenatal Care in Emerging Adult Latinas

Abstract: Despite efforts to improve access to prenatal care, emerging adult Latinas in the United States continue to enter care late in their pregnancies and/or underutilize these services. Since little is known about emerging adult Latinas and their prenatal care experiences, the purpose of this study was to identify actual and perceived prenatal care barriers in a sample of 54 emerging adult Latinas between 18 and 21 years of age. More than 95% of the sample experienced personal and institutional barriers when attemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…Personal barriers can be expanded to include individual or psychological factors, patient knowledge and attitudes, and socioeconomics. There are a number of individual or psychological barriers to obtaining prenatal care, such as not feeling well or having low energy or fatigue (Torres 2016); depression (Daniels Noe and Mayberry 2006); life stress, chaos or crises (Heaman et (Daniels et al 2006). Women may also delay prenatal care while considering abortion (Johnson et al 2011;Torres 2016), out of fear of pregnancy disclosure (Braveman et al 2000), or due to negative emotional responses to pregnancy (Daniels et al 2006;Torres, 2016).…”
Section: Personal Motivators and Barriersmentioning
confidence: 99%
See 2 more Smart Citations
“…Personal barriers can be expanded to include individual or psychological factors, patient knowledge and attitudes, and socioeconomics. There are a number of individual or psychological barriers to obtaining prenatal care, such as not feeling well or having low energy or fatigue (Torres 2016); depression (Daniels Noe and Mayberry 2006); life stress, chaos or crises (Heaman et (Daniels et al 2006). Women may also delay prenatal care while considering abortion (Johnson et al 2011;Torres 2016), out of fear of pregnancy disclosure (Braveman et al 2000), or due to negative emotional responses to pregnancy (Daniels et al 2006;Torres, 2016).…”
Section: Personal Motivators and Barriersmentioning
confidence: 99%
“…There are a number of individual or psychological barriers to obtaining prenatal care, such as not feeling well or having low energy or fatigue (Torres 2016); depression (Daniels Noe and Mayberry 2006); life stress, chaos or crises (Heaman et (Daniels et al 2006). Women may also delay prenatal care while considering abortion (Johnson et al 2011;Torres 2016), out of fear of pregnancy disclosure (Braveman et al 2000), or due to negative emotional responses to pregnancy (Daniels et al 2006;Torres, 2016). Also, this may include not knowing or believing that prenatal care is important (Heaman et al 2015;Torres 2016); not knowing when to start prenatal care (Braveman et al 2000); or having a negative attitude toward prenatal care (Mazul et al 2017).…”
Section: Personal Motivators and Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research documents that Mexican immigrants experience a reduction in healthcare access after they migrate to the United States and continue to face more challenges in accessing health care as compared to the non-migrant population [22]. A small study of Latina youth found that over 95% of the sample experienced personal and institutional barriers when attempting to access prenatal care [23].…”
Section: Background and Signi Cancementioning
confidence: 99%
“…This recommendation, however, does not address issues pertaining to gaps in treatment or the limited supply of perinatal mental health specialists. For example, although obstetricians are able to prescribe psychotropic medications that are safe in pregnancy, usually several weeks have passed between the time a patient learns that she is pregnant and the time she presents to an obstetrician for prenatal care (7). During this time, the patient may have stopped taking her previously prescribed antidepressant medications (4).…”
mentioning
confidence: 99%